ZnO Nanostructures to Detect Low Concentrations of Indoor Pollutants. (2015) - Gonzalez-Chavarri, J.; Castro-Hurtado, I.; Castaño, E.; Mandayo, G.G.
Abstract: The aim of this work is to develop an easy-to-manufacture and highly-sensitive conductometric microsensor for indoor air quality (IAQ) monitoring. The sensing device consists on ZnO nanostructures on Pt interdigitated electrodes and a Pt heater surrounding the sensing layer, fabricated on one side of a 2.5x2.5 mm 2 alumina substrate. ZnO nanostructures are grown in-situ over the electrodes, using the Vapour-Solid (VS) approach. The samples were tested under different concentrations of benzene, formaldehyde, carbon monoxide and nitrogen dioxide, showing significant response to low concentrations of the four gases.